Turks and Crimean Tatars in the works of Juraj Križanić - Krzyżosiak, Romuald (Balcanica Posnaniensia. Acta et studia, 2007)
The issue of the Turks and Crimean Tatars occupies a special place in the political journalism of Juraj Križanic (1618–1683), a Croatian clergyman and ideologist of Slavic unity. The author of the article analyses the political views of this thinker, who perceived the Turkish-Tatar threat in the context of the intensification of Russian policy in the Black Sea region. The source material is based on Križanic's writings, including his treatise Politika (Discussions on Government), memoirs, and historiographical studies on Pan-Slavic ideas. Križanic regarded the Crimean Tatars as the most dangerous enemies of the Slavs, even more dangerous than the Turks. He expected Russia to launch an offensive against the khanate and at the same time create a broad coalition of Christian peoples of South-Eastern Europe. J. Križanić developed a detailed plan for the conquest of Crimea and its colonisation by the Slavs. His position on Turkey was less precise. His projects were utopian in nature and were never realised, but they were in line with the broadly understood Slavic ideas.